Introduction to Asymptotic Giant Branch Stars and their Significance - Eid, Mounib F. El (Current Research Progress in Physical Science Vol. 3, 2024)
A compact review of the main characteristics of asymptotic giant branch stars (briefly: AGB) will be described. We describe a link with observations and basic features of theoretical modeling of these important evolutionary phases of these stars. The AGB stars are the progenitors of white dwarfs in the galaxy, and they produce about half of the heavy elements and their isotopes beyond iron element via the s-process nucleosynthesis, which is a slow neutron-capture process linked to \(β\) radioactive decay. The essential neutron source is mainly due to the 13C(\(α\),n)16O reaction, and to a lesser extent the 22Ne(\(α\),n)25Mg reaction. In addition, several important elements are produced such as 19 F and 27 Al during the thermal pulsation of the stars. The summary in sect. 6 contains the most important aspects of the AGBs. It is a challenging astrophysical problem to describe the process of convective mixing coupled to nuclear reactions during thermal pulsations including the effect of the magnetic field to obtain the right amount of 13 C that can lead to s process abundances compatible with observation. Important remaining problems are presented in the present work.